Leadership Style in Improving Learning - Muis, Abdul; Ahyani, Nur; Kesumawati, Nila (Jurnal Pendidikan Tambusai, 2021)
This study aims to describe the principal's leadership style in improving the learning process at SD Negeri 05 Ogan Komering Ulu. This research uses qualitative methods with a descriptive approach. Data techniques through observation, interviews, and documentation. The research subjects were school principals and teachers of SD Negeri 05 OKU. The results of this study indicate that the principal leadership style applied in SD Negeri 05 Ogan Komering Ulu was carried out by the principal in general in response to good cooperation by subordinates, who used the democratic-participatory leadership style shown by the principal gave an example that both for teachers so that teacher personality increases, assigning or delegating teachers identically to official duties and motivating students, and is open and becomes a place of consultation for teachers and students in order to realize the quality of education and learning.